THE RELATIONSHIP BETWEEN PARENTING PATTERN AND THE PERFORMANCE TREATMENT INDEX (PTI) - Sity Noormazidah; Isnur Hatta; Diana Wibowo; Ika Kusuma Wardani; Galuh Dwinta Sari (Universitas Lambung Mangkurat, 2024)
Background: Parent parenting is a way of parents in making a series of positive efforts in educating and developing their children. Parental parenting patterns have three: democratic (authoritative), authoritarian (authoritarian) and permissive. Good parenting patterns affect the actions of people in maintaining their fixed teeth called Performance Treatment Index (PTI) which is the percentage of the number of fixed teeth carried out by a shed or patching of the DMF-T number. The percentage of damaged, perforated and painful teeth in Banjar Regency ranks eleven, namely 43.34% and the percentage of patched teeth / dens is 5.65% this is the third lowest among the districts in South Kalimantan. Purpose: Analyzing parental parental pattern relationships with Performance Treatment Index (PTI) in MTsN 1 Banjar District Gambut Banjar Regency. Methods: This research is by observational analytics method with cross-sectional approach. The sampling technique uses simple random sampling with a sample number of 36 people research. Test the analysis using SPSS application by Spearman method. Results: The results show that most parents apply democratic (authoritative) parenting patterns. Performance Treatment Index (PTI) students are considered bad, and not obtained parents with authoritarian parenting (authoritarian) parenting patterns. Spearman test results showed no connection between parenting patterns and Performance Treatment Index (PTI) students (p value = 0.320). Conclusion: The parenting patterns applied by parents are more democratic (authoritative) types and there is no connection between parenting patterns and Performance Treatment Index (PTI).